TRANSITION TO LOCAL EQUILIBRIUM IN THE DEVELOPMENT OF A DIFFUSIONAL BIMETASOMATIC ZONE - Balashov V.N.; Lebedeva M.I. (My University, 1989)
One promising area of theoretical research on metasomatism is the development of a macrokinetic model based on reversible reactions. The present paper describes a numerical investigation of a model of bimetasomatism in isothermal systems with solid two-component mineral phases of constant composition. The interstitial phase transporting the components is a dilute hydrothermal solution. The pressure on the minerals is constant and equal to the pressure of the interstitial solution. Under these conditions the chemical potential of water is governed almost exclusively by P and T.